Unsanctioned techniques for having sickness certificates accepted: a qualitative exploration and description of the strategies used by Swedish general practitioners - Mani Shutzberg (Taylor & Francis Group, 2019)
Objectives: To explore informal and unsanctioned techniques general practitioners (GPs) employ as a means to increase the likelihood of sickness certificate approval, following the Swedish Social Insurance Agency's (SSIA's) consolidation of the gatekeeping role in sickness benefit evaluation. Design: Qualitative semi-structured interviews with 20 GPs working in Swedish primary care. A thematic analysis of the transcribed material was carried out to map different techniques employed by the practitioners. Results: Eight techniques were identified, particularly with respect to the way in which the sickness certificate is written to ensure approval by the SSIA. The identified techniques were most commonly adopted when the patient's case was perceived to be at high risk for rejection by the SSIA (such as psychiatric illnesses, chronic pain etc.). Conclusions: The findings imply that the informal and unsanctioned techniques are complex and ambiguous. They are used intentionally and covertly. The study also suggests that, while the consolidation of SSIA's gatekeeping role may have resolved some sickness absence issues, a consequence may be that GPs develop unsanctioned techniques to ensure compliance.